DESIGN METHOD AND THEORETICAL ANALYSIS FOR WHEEL-HUB DRIVING SOLAR TRACTOR - Zhang, Chao; Gao, Huisong; Deng, Xiaoting; Lu, Zhixiong; Lei, Yi; Zhou, Huadong (Emirates Journal of Food and Agriculture, 2017)
Burning fossil fuels to produce greenhouse gases, leading to global climate change. The sustainable development requires to design a environmentally benign tractor, which have no or little air pollution during operation. Considering these constraints, Presents a wheelhub driving solar tractor design method, includes the integral structure design and the main components choose,such as hub moter, battery, gearbox, etc.,and put forward cumulative operation time throughout the day (COTTD) as solar tractor working ability evaluation index. Combined with the local meteorological, predicted the generation capacity of photovoltaic (PV) array in different time of the year, 1.19 kWh/d in winter and 3 kWh/d in summer. Analysis the COTTD relationship with speed of tractor, mass of tractor, slope of road under different work conditions. When the operating speed increases, the trend of COTTD is shortened. Under the same conditions, the COTTD in winter is significantly shorter than the summer. When the speed is 6 km/h on flat road, the COTTD will decrease with the total mass increase. The slope of the road has great influence on COTTD. This research provides valuable technology reference for solar tractor system design and optimize control.